Feiras livres de Cascavel e de Ocara: Caracterização, análise da renda e das formas de governança dos feirantes - Coêlho, Jackson Dantas (2008)
It was looked for to identify, in this work, the characteristics that differentiate the merchants that act in free markets of cities with different levels of development (Cascavel and Ocara). Primary data were collected in questionnaaires applied with the merchants; some statistical tests confirmed the absence of significant difference for some lifted up variables, with base in the comparison of the cities for the criterion of IDH, reason for which the cluster analysis was adopted for best differentiate the merchants. Among the reached results, stand out; the more adopted purchase forms are the cash sale and pay after sold the merchandise, for the merchandise not produced by the merchant. The type of sold product, the proximity of Ceasa, limited edafo-climatic conditions for agricultural products, middlemen's existence, the merchant's socioeconomic condition and means inthe merchandise purchase are factors that influence the governance form of the merchants transactions. Was ended that, in the Cascavel, the merchants depend less on the government transfers, and in Ocara, that dependence is larger, but smaller than it was imagined; the capital stock level among the merchants is very low; in infrastructure terms, Ocara's fair needs larger attention, given the lack of the basic, as a public market with points of water and bathrooms; Cascavel's fair, in spite of the existent infrastructure, also needs improvements, mainly in animals fair, in the subject of the cleaning, installation of equipments, night surveillance and standardization of clothing stands; and that BNB could study financing possibilities for the prone merchants to request loans – the ones that work with fruits and vegetables, pork/mutton or fish – and that, not being a producer, he/she buys the merchandise of no relatives producers or middlemen of out of the city, paying after sold the merchandise, in Cascavel, and the ones that sell alive animals or fish, buying to his/her view merchandise of middlemen of the city or no, in Ocara.